2009
DOI: 10.1007/s11605-008-0667-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life after Colonic Resection for Diverticular Disease: Long-term Results

Abstract: Our results indicate that there does not seem to be any long-term advantage to colonic resection which should be considered only in patients presenting complicated DD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 22 publications
(29 reference statements)
4
29
0
1
Order By: Relevance
“…We did not compare our collective to a group with conservative treatment. Several authors argue that uncomplicated diverticular disease takes a benign course in the long run and view the operative treatment critically [13,22,23]. However, not all of them addressed patient-reported outcome but concentrated on objective clinical data, especially assessing the rate of patients with unsuccessful conservative treatment, presenting with complicated disease after conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We did not compare our collective to a group with conservative treatment. Several authors argue that uncomplicated diverticular disease takes a benign course in the long run and view the operative treatment critically [13,22,23]. However, not all of them addressed patient-reported outcome but concentrated on objective clinical data, especially assessing the rate of patients with unsuccessful conservative treatment, presenting with complicated disease after conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we know that up to 20% of patients complain of persistent abdominal pain after surgical treatment of diverticulitis [32], and the quality of life of those patients is significantly worse [33]. It has been hypothesized that persistent symptoms are linked to increased pro-inflammatory cytokines with persistent chronic inflammation in mucosal biopsy samples, as recently confirmed by Lahat et al [15].…”
Section: Inflammationmentioning
confidence: 95%
“…Those authors postulated that a more expectant approach results in fewer deaths and fewer colostomies and is costsaving for both younger and older patients [19]. Scarpa et al found the same quality of life, symptom frequency, and operation and hospital admission rate in operated and nonoperated patients (study with 71 patients, follow-up 3,9 years) [20].…”
Section: Surgically Treated Patientsmentioning
confidence: 99%